Travel Intention Of International Tourists To Jordan In Post-Pandemic - Mheidat, Mohammad Zein Eddin Faleh (2024)
Covid-19 has disrupted international travel due to which the tourism sector in jordan has seen a drop in the number of international tourists, who represent the main source of tourism income which is a significant contributor to the gross domestic product (gdp). There are limited studies that have investigated the significant impact of pandemic-related factors on tourist travel intention post-pandemic from tourists' perspective. Considering the significance of this issue, the study examined the influence of travel motivation, risk perception, and destination image of international tourists who visited jordan post-pandemic to predict their future travel intention. A questionnaire was used to collect data from the tourists. In this regard, 460 questionnaires were distributed among the tourists between 4th and 31 december 2022 through e-mails, social media channels, official tourism websites, and accommodation sites. In this study, 290 questionnaires were used for data analysis. Pls-sem has been used for the hypotheses testing. The results found that travel motivation and destination image have a significant influence on travel intention to visit jordan post-pandemic. Whereas, risk perception did not significantly influenced travel intention. The findings can help tourism policymakers and industry practitioners to develop effective strategies to attract more visitors to the country and promote sustainable destination after crisis.